Pengaruh Kinerja Individual, Pemanfaatan Teknologi, Kemampuan Teknik Personal dan Dukungan Manajemen Puncak terhadap Efektivitas Penggunaan Sistem Informasi Akuntansi - Winda Ayu Amelia; Tumirin Tumirin (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Study This aim for test influence individual performance, utilization technology, capabilities personal techniques, and support management peak to effectiveness use system information accounting. Study This use approach quantitative with method taking sample that is purposive sampling and samples obtained by 50 respondents. Population in study This is employee part finance or relate with accountancy companies in the Gresik Region. Data used in study This is primary data in the form of questionnaire. Technique analysis of the data used is multiple linear regression tool test used is the SPSS Version 25.0 program. results from study This show that variable individual performance and utilization technology No influential to effectiveness use system information accounting, variable ability influential personal techniques positive and significant to effectiveness use system information accounting, meanwhile variable support management peak Also No influential significant to effectiveness use system information accounting.